The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1471-0528.2010.02749.x
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 infection in human pregnancy

Abstract: Human parvovirus B19 infection is widespread. Approximately 30-50% of pregnant women are nonimmune, and vertical transmission is common following maternal infection in pregnancy. Fetal infection may be associated with a normal outcome, but fetal death may also occur without ultrasound evidence of infectious sequelae. B19 infection should be considered in any case of nonimmune hydrops. Diagnosis is mainly through serology and polymerase chain reaction.Surveillance requires sequential ultrasound and Doppler scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 207 publications
2
139
0
6
Order By: Relevance
“…Of these, 7 (63.6%) were moderately to severely anaemic with 57.1% of them presenting with malaria as well. Two (18.2%) of the B19V viraemic subjects had mild anaemia, both of whom had malaria as well whereas the remaining 2 (18.2%) of the B19V infected individuals were non-anaemic and did not have malaria either.…”
Section: Co-infection With B19v and Malaria And Its Association With mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 7 (63.6%) were moderately to severely anaemic with 57.1% of them presenting with malaria as well. Two (18.2%) of the B19V viraemic subjects had mild anaemia, both of whom had malaria as well whereas the remaining 2 (18.2%) of the B19V infected individuals were non-anaemic and did not have malaria either.…”
Section: Co-infection With B19v and Malaria And Its Association With mentioning
confidence: 99%
“…In addition, some case studies have also reported of B19V induced severe anaemia following malaria infection and successful treatment with antimalarials [46][47][48][49][50] . Though it is primarily known to cause erythematous rash, foetal hydrops and other involvements in various haematological disorders, B19V is also involved in other conditions [34,[51][52][53][54][55][56][57] . B19V in many occasions have been reported as a bystander or contributor to many conditions such as hepatitis, myocarditis, arthritis among others [58][59][60][61][62][63][64][65][66][67] .…”
Section: P E E R R E V I E W Abstractmentioning
confidence: 99%
“…Erythema infectiosum, chronic arthritis, spontaneous abortion, hematological disorders, myocarditis, and glomerulonephritis are only some of these (1)(2)(3). B19 is spread from person to person by infected respiratory secretions, by infected blood and blood-product transfusions, and by vertical transmission from mother to fetus (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal parvoviral seroconversion rates vary between 3% and 34% and the risk of vertical transmission is approximately 30% 3,4 . Fetal hydrops develops in 0-12.5% of infected fetuses with a peak between 17 and 24 weeks' gestation, while fetal demise is estimated to occur at a rate of 5-10%, with or without the diagnosis of fetal hydrops in cases of unclear pathophysiology 3 -5 .…”
Section: Cause Of Fetal Demise In First-trimester Parvovirus Infectiomentioning
confidence: 99%
“…Fetal hydrops develops in 0-12.5% of infected fetuses with a peak between 17 and 24 weeks' gestation, while fetal demise is estimated to occur at a rate of 5-10%, with or without the diagnosis of fetal hydrops in cases of unclear pathophysiology 3 -5 . We consider that there are three hypothetical causes of fetal demise in first-trimester parvovirus fetal infection: 1) primary viral infection of the myocardial cells initially causes myocarditis, leading to hydropic cardiac failure and demise; 2) bone marrow transient aplastic crisis occurs as the primum movens for anemia, leading to the sequence of congestive heart failure/hydrops/death; 3) placentitis without fetal infection causes placental dysfunction and ultimately fetal demise 3,4 .…”
Section: Cause Of Fetal Demise In First-trimester Parvovirus Infectiomentioning
confidence: 99%